2017
DOI: 10.3926/jotse.276
|View full text |Cite
|
Sign up to set email alerts
|

Meaningful learning using concept maps as a learning strategy

Abstract: This work presents a proposal for the teaching-learning of the concept map technique applied to the Natural Sciences course in the second year of Compulsory Secondary Education (ESO, according to its initials in Spanish). Two sessions have been designed, one of which is an instructor-led session to learn the technique and another is a session in which the students independently create a concept map, applying what they have learned in the previous session. To determine the effectiveness of the proposal, the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 7 publications
4
23
0
1
Order By: Relevance
“…Moreover, according to the students, the result of the concept map is more comfortable than the volume of concept. In Romero, Cazorla and Buzon (2017), they aimed to learn the concept maps in the second stage and found that this goal was achieved as a result of the study. They found the availability of the concept map in the classroom environment.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, according to the students, the result of the concept map is more comfortable than the volume of concept. In Romero, Cazorla and Buzon (2017), they aimed to learn the concept maps in the second stage and found that this goal was achieved as a result of the study. They found the availability of the concept map in the classroom environment.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 shows a brief description of the design methodologies that were used in carrying out this research (Dignan, 2011;Hanington & Martin, 2012). In most of them, the use of concept maps as a learning and working strategy is a common characteristic (Romero, Cazorla & Buzón, 2017).…”
Section: Design As a Tool For Science Educationmentioning
confidence: 99%
“…Concept maps are top-down diagrams that show relationships between concepts, including cross-links between concepts and examples, and show systematic relationships between related subconcepts [34]. The use of the concept maps makes students more systematic in learning [35]. The purpose of this task is to make the learning of the Quantitative Research Methodology course run more smoothly because they have prepared themselves by studying the material to be taught that day.…”
Section: Improvement In the Composition Of Course Materialsmentioning
confidence: 99%